Facility Closure: How to Get In, Get Out, and Get What Is Important - Lail, Pamela J. (Perspect Health Inf Manag, 2016)
This article examines the current state of affairs of the health information management role in facility closure as well as the impact on revenue cycle operations. Health information management professionals are uniquely positioned to assist an organization in closure efforts because of their knowledge of revenue cycle operations, ability to work with the software products used to generate and store patient information, and solid understanding of the process of care and treatment of the patient. This information is integral to ensuring that patient information in a variety of formats and locations is properly secured and saved so that it will be available to patients and caregivers who need it after the facility closes. This article also goes into detail concerning some of the financial tasks required to be completed when a facility closes because the required data come from coded information or, in the case of the Worker Adjustment and Retraining Notification (WARN) Act, affect how employees will be compensated. This article provides a detailed look at the process to help guide other health information management professionals in a diverse set of care environments in the process of facility closure.